Understanding the Fintech Wave: A Search for a Theoretical Explanation - Mirchandani, Anita; Gupta, Namrata; Ndiweni, Esinath (International Journal of Economics and Financial Issues, 2020)
The recent rise in the number of ‘Fintech’ companies is set to transform the financial services industry on a global scale. Fintech companies create more competitive advantages in the financial market by providing faster services in the field of payment, financial consultancy, lending, and investment. Many countries have joined the bandwagon of adopters; however, little is known about the factors behind their success. Therefore, this paper attempts to investigate the key factors that underpin the success of Fintech across the various financial sectors and highlight the challenges they pose to traditional banks. Due to limited scholarly work on the subject the paper conducts a meta syntheses of ten published global survey reports conducted by consultants such as PwC (2016; 2017;2019), Capgemini (2017), Ernst &Young (2017; 2018; 2019); KPMG (2019) etc. and relevant data from International Monetary Fund and World Bank reports (2019). We identified the key enablers and disablers of Fintech and classified them into macro and micro factors. We concluded that the success of Fintech is context dependent on the political, cultural and environmental factors in the adopting nation. Keywords: Fintech, Macro and Micro enablers; Context dependent; Disruptors JEL Classifications: E44, G1, G2 DOI: https://doi.org/10.32479/ijefi.10296